A Novel Isopimarane Diterpenoid with Acetylcholinesterase Inhibitory Activity from Nepeta sorgerae, an Endemic Species to the Nemrut Mountain - TOPÇU, GÜLAÇTI; Yilmaz, Anil; Caglar, Pinar; Dirmenci, Tuncay; Goren, Nezhun; Topcu, GÜLAÇTI (My University, 2012)
From the dichloromethane extract of Nepeta sorgerae, the isolation and structure elucidation are now reported of a new isopimarane diterpenoid, named sorgerolone, and two known triterpenoids, oleanolic acid and ursolic acid. Antioxidant activity of the extracts and the isolated terpenoids was determined by the DPPH free radical scavenging and lipid peroxidation inhibition (beta-carotene bleaching) methods. Anticholinesterase activity of the extracts and isolates was investigated by Ellman-s method against AChE and BChE enzymes. Although the antioxidant activity results were low, the AChE enzyme inhibition of the extracts and terpenoids was very promising.